Factors influencing the job satisfaction of millennials in China's financial industry - MIAO, QIMING (2022)
In contemporary society, job satisfaction plays an essential role in human resource management. Millennials are gradually becoming the main force of the labor market, and millennials of China have experienced the rapid development of the financial industry, which is full of opportunities and challenges. Hence, based on relevant motivation theories and previous studies, the main purpose of this research is to explore how millennials in China’s financial industry perceive the factors that affect job satisfaction. The factors include salary, working hours, training and development, working environment, and leadership. This research adopts a qualitative research method, and data are collected through online semi-structured interviews with twelve participants in China’s financial industry. The research found that Chinese millennials attach great importance to a fair salary distribution system, work-life balance, and an appropriate and equitable training and development mechanism. Working environment and leadership, as new factors derived from interviews, are also positively correlated with millennials’ job satisfaction in China’s financial industry. The research results not only fill the gap of previous literature but also provide suggestions for future research and human resource management practice.